PEMANFAATAN DONGENG LET’S READ UNTUK SISWA SEKOLAH DASAR DALAM MENINGKATKAN PEMAHAMAN PERILAKU HIDUP SEHAT - Harpiana Rahman; Harnita Rahman; Zulkhair Burhan; Selia Dwi Kurnia (Pusat Standar dan Kebijakan Pendidikan, BSKAP, Kemendikbudristek, 2022)
Health education in elementary schools (DS) which is implemented the behavior of clean and healthy life (PHBS) unable to develop the potential of students to to behave healthy consciously. The development of the concept of PHBS education in schools is implemented just by socialization and provide. So that the strategy is considered not enough to improve health literacy in students. Based on this analysis, the use of fairy tales as a means of health education in elementary schools was chosen as a smart practice in the development of education and health promotion which aims to meet the needs of students in understanding health information, especially the urgency of implementing PHBS. To measure the effectiveness of fairy tales, the measurement of knowledge change is measured by qualitative method with pre and post tests. Through this method, it was found that students who were exposed to fairy tales selected from the Let's Read application experienced a change in their level of knowledge. Before the fairy tale was held, students did not understand the values of PHBS at school. However, after the fairy tale activity, the students' knowledge level is at sixth level knowledge that students not only understand well the concept of PHBS, but students have the ability to create PHBS information well.